2021
DOI: 10.20511/pyr2021.v9nspe3.1265
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of BYOD on Results of Students' Learning

Abstract: This work analyzes the influence and efficiency of BYOD for learning students and academic perfection. The relevance of mobile technologies for learning has been substantiated. The influence of BYOD on academic performance of undergraduate students in terms of their test scores and final course marks, as well as on quality of work on selected course projects and on level of satisfaction with the BYOD course, has been experimentally studied. It has been proved that BYOD exerts positive influence on learning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Research that was conducted in [28] found that BYOD had given positive influence on learning and academic achievements of students and BYOD also give impact in stimulating and motivating students that will affect the level of students' performances and creation of independent learning. E-learning users believe that highquality educational services are acceptable, and that a secure atmosphere for these systems might help them feel more useful [29].…”
Section: Byod In Educationmentioning
confidence: 99%
“…Research that was conducted in [28] found that BYOD had given positive influence on learning and academic achievements of students and BYOD also give impact in stimulating and motivating students that will affect the level of students' performances and creation of independent learning. E-learning users believe that highquality educational services are acceptable, and that a secure atmosphere for these systems might help them feel more useful [29].…”
Section: Byod In Educationmentioning
confidence: 99%